Vitamin E-bonded membrane a further step in dialysis optimization - Ronco, Claudio 1951-; Greca, Giuseppe la (Contributions to nephrology, 1999)
In recent years, major concerns have been expressed about long-term derangements in hemodialysis patients and possible clinically relevant blood-membrane interactions. Preliminary studies employing biocompatible membranes and antioxidant agents such as vitamin E have demonstrated significant improvements in patient organ function and hemopoietic capacity with increased hematocrit and quality of life. Using a new technology, vitamin E has now been successfully bound to the inner surface of a hollow-fiber membrane, so that the patient’s blood is flowing in contact with a layer of antioxidant agent covering the inner surface of the membrane in the hemodialyzer.The opening chapters of this publication give an overview on oxidant stress and the role of vitamin E as antioxidant agent and elaborate on technical aspects, hydraulics and permeability characteristics of the membrane in question. The main part is dedicated to the hemocompatibility of the membrane, its effect on erythrocyte morphology and survival and the impact on white cell and platelet function. The metabolic effects and the antioxidant impact of the vitamin E-coated membrane are presented in the last part of the book.Intended as a reference tool for professionals, students and fellows involved in the care of end-stage renal disease patients, it is also hoped that this book serves as a starting point for further speculations and research in the field